The removal of unburned carbon from fly ash by kerosene extraction - Sung, H.; Yoo, Kyoungkeun; Lee, S. (Taylor & Francis, 2016)
The recycling process was developed to remove and recover unburned carbon from fly ash using kerosene extraction. The effects of experimental factors such as shaking time, initial unburned carbon content, and organic to suspension (O/S) ratio on the removal of unburned carbon were investigated to obtain the optimum conditions. The results indicate that the removal ratio of unburned carbon increased with increasing shaking times and decreasing the initial unburned carbon content, but the residual amount of unburned carbon was independent of O/S ratio. The content of unburned carbon decreased successfully to less than 3% under the following conditions; 15 min in shaking time, 10% in pulp density, 30 °C in temperature, 200 rpm in shaking speed, and 0.5 in O/S ratio.